If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+20=(x+4)x
We move all terms to the left:
5x+20-((x+4)x)=0
We calculate terms in parentheses: -((x+4)x), so:We get rid of parentheses
(x+4)x
We multiply parentheses
x^2+4x
Back to the equation:
-(x^2+4x)
-x^2+5x-4x+20=0
We add all the numbers together, and all the variables
-1x^2+x+20=0
a = -1; b = 1; c = +20;
Δ = b2-4ac
Δ = 12-4·(-1)·20
Δ = 81
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{81}=9$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(1)-9}{2*-1}=\frac{-10}{-2} =+5 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(1)+9}{2*-1}=\frac{8}{-2} =-4 $
| 2(u+7=42 | | 5.11*10^-6=(x)(0.0004+4x^2) | | 6v-10=4v-1 | | 15=11x-9 | | 2s+4s=7+2s | | -16=r-2 | | 7v-6v=-69 | | 18(-3y+5/2)-3y=-4 | | 9y+5=-15-y | | -9(5z-4z-6)=78 | | s8=-5 | | 7u+5=5+5u | | 3m+21=6m+2 | | 7/6=x | | 2(9x-4)=7x+4 | | 2x^2=115 | | -2.q=-9.2 | | 6d=100 | | y-60/y=4 | | -492n-5)=-8n-20 | | 7x-1/4=-9 | | 7+9m=10m+1 | | -3x+5=x+21= | | 5x-3x+8=3x+9 | | 22y-3=85 | | 0.4v=1.8 | | 6(x-10)=-24 | | 4x+5(7x=-3)=9(x-5) | | 14(x-3)-22x=-22 | | 27c-45=36c-9 | | 6;n= | | 31x-9=270 |